A CASE OF MYXOFIBROSARCOMA OF THE DIAPHRAGM - NAGATA, Chieko; SAIMURA, Michiyo; MITSUYAMA, Shoshu; ABE, Yuji; TAMAE, Keiyoshi; MATSUURA, Yasuo; YAMAMOTO, Ichiro (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2006)
We report a rare case of myxofibrosarcoma of the diaphragm. A 45-year-old woman complaining of dull pain in the left hypochondrium was admitted to our hospital, because she was pointed out a left abdominal tumor on ultrasonography at another hospital. Abdominal CT and MRI revealed a discrete tumor about 17cm in diameter in the left hypochondrium, which compressed the stomach, spleen, pancreas, and left kidney. Angiography disclosed that the tumor was fed from the left subphrenic artery. Operative findings showed that the tumor had arisen from the diaphragm, and we performed the tumor resection combined with the spleen and part of the diaphragm. The histopathological diagnosis was myxofibrosarcoma (myxoid malignant fibrous histicytoma). She is under adjuvant chemotherapy with MAID (MESNA+ADM+IFM+DTIC), and has no recurrence, as of two months after the surgery.